THE ROLE OF SOCIAL RESPONSIBILITY IN THE USE OF ARTIFICIAL INTELLIGENCE IN THE MARKETING ACTIVITIES OF AN ENTERPRISE - SHUBA, Tetiana; BOLOTNA, Oksana; VITOV, Oleksandr; KUDREVICH, Alina (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article defines the role of the ethical aspect of introducing artificial intelligence-based technologies into the marketing activities of modern companies. It is established that AI-based marketing relies heavily on the collection and analysis of personal data. The main ethical challenges of using artificial intelligence are identified. Recommendations on how to overcome these challenges are provided.Over the past decade, artificial intelligence (AI) has entered various industries. Today, AI is a general-purpose technology that can affect every industry and transform the economy. Against this backdrop, there is a rapidly growing body of academic literature documenting the business potential of AI and big data. The era has witnessed a dramatic increase in the number of AI and machine learning (ML) tools, applications, and platforms. These technologies have had an impact on healthcare, manufacturing, law, finance, retail, real estate, accounting, digital marketing, and several other industries.Ukrainian businesses are actively using artificial intelligence in their marketing strategies. For example, large IT companies and startups are implementing chatbots to automate customer support, while retailers are using recommender systems to improve the user experience.On the other hand, AI in marketing is an extremely powerful force for improving business performance. The more it develops, the more fully and deeply it is expected to be implemented in the daily operations of organisations. In Ukraine, AI is actively used in the development of marketing strategies. Large IT companies and startups use chatbots to provide automatic customer support. At the same time, retailers are implementing recommendation systems to improve user experience. AI in marketing, as an active accelerator of business efficiency, is becoming more and more integrated into everyday organisational activities.Companies are investing in AI research to find out how they can make AI closer to humans. By 2025, AI software revenues alone will reach more than $100 billion worldwide. This means that we will continue to see the development of AI and machine learning (ML) technologies in the foreseeable future. AI is changing very fast, so it will take a lot of effort to keep up with the latest trends.
Keywords: artificial intelligence; ethical aspect; marketing technologies; corporate social responsibility; marketing strategies